2013
DOI: 10.2139/ssrn.2372066
|View full text |Cite
|
Sign up to set email alerts
|

Intangible-Driven Value Creation: Supporting and Obstructing Factors

Abstract: This study investigates the factors that support or obstruct market value creation through intangible capital. We explore the impact of intangibles and exogenous shocks on corporate attractiveness for investors measured by Market Value Added (MVA). Specifically we analyze relationship between intangible-driven outperforming of companies, measured by Economic Value Added (EVA) and a number of intangible drivers on macro, meso and micro level. We suppose that the process of value creation is confined not only by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Shakina and Molodchik (2014) confirmed that the individuality of a company plays a considerable role in the effective use of intangible capital.…”
Section: Theoretical Backgroundmentioning
confidence: 76%
See 4 more Smart Citations
“…Shakina and Molodchik (2014) confirmed that the individuality of a company plays a considerable role in the effective use of intangible capital.…”
Section: Theoretical Backgroundmentioning
confidence: 76%
“…Dependent on accounting rules, several studies (Moeller, 2009;Zéghal and Maaloul, 2010;Kianto et al, 2013;Tsai et al, 2013b;Salchi et al, 2014;Shakina and Molodchik, 2014;Tudor et al, 2014;Vallejo-Alonso et al, 2015) have identified and measured the impact of intangibles on value-creation and performance in business.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations